1994
DOI: 10.1111/j.1365-2249.1994.tb07018.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant gp120 induces IL-10 in resting peripheral blood mononuclear cells; correlation with the induction of other cytokines

Abstract: SUMMARYImmutiological abnotmalities present in HIV-1-infected individuals often reflect an imbalance of cytokine production. The HIV-I gpl20 has the ability to induce a number of cytokines, and to enhance immunoglobulin release by normal peripheral blood mononuclear cells (PBMC) in vitro, in the absence ofIL-2 production and of lymphoproliferation. This study provides evidence that gpl20 is a potent IL-10 inducer in normal PBMC cultures. The pattern of other cytokines induced by gp 120 includes interferon-alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…21 To our knowledge, this is the first study to find an association between gp120 concentration and cytokine levels in the plasma of HIV-infected individuals. The mechanisms by which gp120 induces cytokines has not been completely defined.…”
Section: 21-23mentioning
confidence: 80%
See 1 more Smart Citation
“…21 To our knowledge, this is the first study to find an association between gp120 concentration and cytokine levels in the plasma of HIV-infected individuals. The mechanisms by which gp120 induces cytokines has not been completely defined.…”
Section: 21-23mentioning
confidence: 80%
“…It has been suggested that binding of gp120 to CD4 on T cells, macrophages, and dendritic cells induces a signaling cascade that up-regulates the production of these cytokines. 7,21 Increased production of these cytokines in HIV-infected subjects with detectable levels of gp120 provides evidence that gp120 contributes to the cytokine dysregulation that is common during primary HIV infection.…”
Section: 21-23mentioning
confidence: 99%
“…Thus, it is essential to determine the viral components responsible for the inflammatory response and to understand the underlying mechanisms and signaling pathways. Several studies have reported the role of HIV-1 proteins, including gp120 [ 18 21 ], Tat [ 22 25 ], Nef [ 26 28 ] and Vpr [ 29 , 30 ] gene products in the immune system dysregulation seen during HIV-1 persistent infection. Some ss-RNA domains expressed by the HIV-1 genome, and HIV-1 gene products act as PAMPs targeting membrane and cytoplasmic PRRs, including TLR2 [ 31 ], TLR3 [ 32 ], TLR4 [ 29 , 33 ], TLR7 [ 34 ], TLR8 [ 35 , 36 ] and RIG-1 [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many HIV-1 proteins that are capable of inducing the production of several cytokines. These proteins include HIV-1 glycoprotein gp120 that induce the secretion of many pro-inflammatory cytokines including IL-1, IL-6, IL-8, TNF-, and IFN- (Francis and Meltzer 1993;Ameglio, Capobianchi et al 1994;Ankel, Capobianchi et al 1994;Capobianchi, Barresi et al 1997). Interestingly, gp120 is also able to induce the secretion of IL-4 and IL-13 in basophils and IL-10 in mononuclear cells.…”
Section: Hiv and Immunological Disordersmentioning
confidence: 99%